From car bombs to logic bombs: The growing threat from information terrorism - Post, Jerrold M.; Ruby, Keven G.; Shaw, Eric D. (Terrorism and political violence, 2000)
The vulnerability of the critical infrastructure has led to increasing concern that it will be the target of terrorist attacks. This article explores definitional aspects of information terrorism and identifies two groups likely to find information terrorism attractive: conventional terrorist groups and information culture groups. As computer sophisticated youth move into the ranks of conventional terrorist groups, the groups will increase their reliance on computer technology, and information terrorism will be incorporated into a hybrid tactical repertoire. Information culture groups, however, confine their attacks to cyberspace. In contrast to the powerful group dynamics of the traditional underground terrorist group, networked groups, particularly information culture terrorists, may only be in contact electronically, and are subject to a radically different group psychology, virtual group dynamics, that significantly affects their decision making and risk taking, and has dangerous security implications.